Male germinal epithelium recovery in mice treated with only dose of Busulfan - Guzmán, Luis (2005)
The DNA replication is disrupted by Busulfan which is a bifunctional alquilant as an ester agent. High dose of this compound are applied before transplants of bone marrow and germ cells. However quantification of the damage to the reproductive system and its recovery have not been established. The aim of this study was to quantify both spermatogenesis and spermiogenesis recovery in mice from damage caused by an injection of Busulfan. We used Balb C mice which were evaluated 30, 54 and 72 days after the intraperitoneal injection of 40 mg/kg body weight. We took the following variables: testicular weight, spermatic concentration in epididimus line and histological cuts to measure the diameter of the seminiferous tubules. Results were analyzed with the test U Mann-Whitney p>0.05. By day 30, testicular weight, spermatic concentration and diameter of the seminiferous tubules were reduced to 77,8%, 97,9% and 34,3% respectively compared to the controls. At day 54, testicular weight and diameter of the seminiferous tubules showed a recovery of 70%. Recovery was complete by day 72. Therefore Busulfan applied in a sigle dose, affects significantly spermatogenesis and the completed recovery takes two spermatic cycles in mice.